Association of Interleukin-17F 7488A/G and 7383A/G Polymorphisms With Rheumatoid Arthritis: A Meta-Analysis - Ping CHEN; Guangqiao HE; Yi YANG; Yanlong YANG; Liangliang LI (Archives of Rheumatology, 2019)
Objectives: This meta-analysis aims to summarize and estimate the relationship between rheumatoid arthritis (RA) susceptibility and two polymorphisms of interleukin-17F (IL-17F) 7488A/G and 7383A/G. Materials and methods: PubMed, Embase and Web of Science were searched up to 01 July 2017. Case-control studies with genotype frequencies data for 7488A/G and 7383A/G were included. The pooled effects were calculated by fixed-effect model or random effects model. Results: A total of seven publications with 1,409 RA patients and 1,303 controls were included in the present meta-analysis. The results indicated that 7488A/G was significantly associated with increased susceptibility to RA (GA vs. AA: odds ratio [OR]=1.43, 95% confidence interval [CI]: 1.07-1.90, p=0.02; GG vs. AA: OR=3.22, 95% CI: 1.54-6.74, p=0.002; GA+GG vs. AA: OR=1.57, 95% CI: 1.02-2.42, p=0.04; GG vs. GA+AA: OR=3.05, 95% CI: 1.46-6.39, p=0.003). In subgroup analysis, 7488A/G was a strong risk factor in Europeans but not in Americans or Africans. No significant association was found between 7383A/G and RA in overall population or ethnic subgroups by all genetic model comparisons. Conclusion: This meta-analysis provided evidence that IL-17F 7488A/G polymorphism is associated with increased RA susceptibility, while no clear correlation was found between 7383A/G and RA.